Spatio-Temporal Geographic Networks for Value Co-Creation and Technology Transfer in China with Patent Data - Yi Su; Ao Lv; Pengfei Zhi; Jiahui Chai; Jingjing Tian (Scientific Data)
Abstract With the increasing complexity of technology, cross-regional joint patent applications and patent transfers have become a prominent component of knowledge activities, attracting substantial attention of academic researchers. To examine the state and distribution characteristics of inter-city knowledge flows, this study utilizes patent data from the China National Intellectual Property Administration database and conducts in-depth data exploration to construct two urban knowledge networks (UKN). Specifically, over 1.23 million value co-creation patents are extracted to develop the urban value co-creation knowledge network (UKN-C), while more than 1.42 million technology transfer patents are refined to establish the urban technology transfer knowledge network (UKN-T). Both UKNs start with cities as nodes and knowledge connections between cities as edges. The edges of UKN-C are weighted by the volume of value co-creation patents, whereas the edges of UKN-T are weighted by the volume of technology transfer patents. To facilitate further research, the geographically explicit and spatial-temporal knowledge flow networks have been released in a simple and accessible format.